Introducing psycholinguistics - Warren, Paul 1958- (Cambridge introductions to language and linguistics, 2013)
"Psycholinguistics is the study of how humans produce and understand language. This textbook provides a clear introduction to the subject and is designed for students with only a basic knowledge of linguistics. It introduces central aspects of the production and comprehension of language, using examples and exercises to reinforce key points. Students will gain an understanding of the processes and representations involved in language use, and how to apply such understanding to the analysis of data. Each of the larger subject areas of language production and comprehension is broken down into stages, such as putting together sentences and finding words. As students investigate these levels and processes, they also explore the interactions between them. They are encouraged to consider what language users might carry around in their heads as part of their linguistic knowledge (what information we store for words, what rule systems we have for generating word and sentence structures, for example), and how this stored knowledge relates to the structures and rules proposed by theoretical linguistics"--Provided by publisher.